TBLT Strategy: Its Effectiveness in TBLT for the Eighth Grade Students at Salsabila Islamic School of Palembang - Yunarti, Yunarti; Syahri, Indawan; Yukamana, Hanni (JEdu: Journal of English Education, 2025)
The research was carried out to investigate the significant effect of the TBLT (Task-Based Language Teaching) and students’ reading motivation on their reading comprehension achievement. The research employed an experimental approach with a factorial framework to investigate the interaction and individual impacts of the variables that were independent. The study population included all eighth-grade students at Salsabila Islamic School Palembang during the 2024–2025 academic years, encompassing four classes with a combined total of 120 students. From this population, a total of 60 students were purposively selected from the population, with 30 students placed in the experimental group and the remaining 30 students in the control group. The data collection methods included a reading motivation questionnaire and reading comprehension tests, both administered as pretests and posttests. The questionnaire, consisting of 20 structured items, aimed to measure the students' levels of reading motivation. The comprehension test consisted of 40 multiple-choice questions, each with five answer options, designed to evaluate the students’ understanding of reading materials. To analyze the data, several statistical techniques were utilized. Specifically, the paired sample t-test, independent sample t-test, and two-way ANOVA were used. All statistical analyses were conducted using SPSS version 22. The results of the hypothesis testing indicated that all four hypotheses yielded statistically significant outcomes, as shown by p-values less than 0.05. Based on these findings, it can be taken the conclusion that the implementation of TBLT strategy has a positive and significant influence on improving students’ reading comprehension. Thus, TBLT is recommended as an effective pedagogical approach in English language instruction, particularly in enhancing reading skills among junior high school students.